(untitled) (Journal of human and social sciences, 2024)
This study aims to identify the obstacles facing the establishment and operation of Islamic banks in Libya, focusing on the city of Misrata. The study adopted a descriptive analytical approach, collecting data through a questionnaire distributed to managers of public banks, internal audit offices, current accounts offices, and academics specializing in financial and administrative sciences. The results revealed the existence of banking, economic, legal, and social obstacles hindering the establishment and operation of Islamic banks. The study recommended the need to develop appropriate accounting systems, establish a specialized department in the central bank, conduct training courses in Islamic economics, and amend laws to suit the nature of Islamic banking operations.